Features of self-esteem formation in adolescence - Nikolaeva, V.V.; Akhmetova, A.E.; Dosbekova, D.E. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article discusses with the problem of self-esteem development in adolescence as an essential component of personality, factors influencing its formation. Scientific approaches to the formation of self-esteem at the stage of adolescence are considered, aimed at the need to solve the problem of preparing the younger generation for living conditions in modern society.
Жасөспірім кезеңдегі өзін-өзі бағалауды қалыптастыру ерекшеліктері
Особенности формирования самооценки в подростковом возрасте
Keywords: adolescence; self-esteem; self-awareness of the individual